Histomorphometric analysis of tissue responses to bioactive glass implants in critical defects in rat calvaria - Cardoso, Ana Karina M. V.; Barbosa, Aryon de Almeida; Miguel, Fulvio Borges; Marcantonio, Elcio; Farina, Marcos; Soares, Gloria Dulce de Almeida; Rosa, Fabiana Paim (Karger, 2006)
The aim of this study was to evaluate the osteogenic behavior of two chemically similar bioactive glass products (Biogran (R) and Perioglas (R)) implanted in critical bone defects in rat calvaria. Thirty-six transfixed bone defects of 8 mm diameter were made surgically in adult male Wistar rats. The animals were distributed equally into three groups: Biogran (GI), Perioglas (GII) and without implant material (control; GIII). The morphology and composition of both bioactive glasses were analyzed by scanning electron microscopy and energy-dispersive spectrometry. Tissue specimens were analyzed at the biological time points of 15, 30 and 60 days by optical microscopy and morphometry, demonstrating biocompatibility for the tested materials with moderate chronic inflammation involving their particles. Bone neoformation resulted only as a reparative reaction to an intentionally produced defect and was limited to the defect's edges. No statistically significant differences among the groups were observed. At the scar interstice, abundant deposits of collagenous fibers enveloping the particles were noted. The present results indicated that the bioactive glasses, under the experimental conditions analyzed, did not show osteogenic behavior. Copyright (c) 2007 S. Karger AG, Basel.
Keywords: bioactive glass; bone regeneration; biomaterials; aloplastic graft